Cassava yield indicators and total organic carbon in tropical soils under different fertilization treatments - Pimentel, Marcelo Laranjeira [UNESP]; Reis, Iolanda Maria Soares; de Castro, Jailson Sousa; Portela, Victor Sousa; Romano, Maria Lita Padinha Correa; Vildoso, Carlos Ivan Aguilar; Gasparin, Eloi; de Sia, Eliandra Freitas (Southern Cross Publishing, 2021)
Cassava is a crop of major socioeconomic importance in Brazil because of its versatility and high yield in nutrient-poor soils. Fertilization can improve soil quality and further increase cassava yield. This study aimed to investigate the effects of different fertilizer sources on soil total organic carbon (TOC) and cassava yield indicators. The experiment was conducted on a family farm in Santarém, Brazil, in a randomized block design, with four treatments and five replications. Treatments were as follows: T1, unfertilized soil (control); T2, NPK fertilizer; T3, poultry manure; and T4, cattle manure. The variables analyzed were soil TOC, shoot fresh weight, plant height, marketable stem diameter, marketable root yield, and yield. Data were subjected to analysis of variance, Tukey’s test (p < 0.05), hierarchical clustering, and principal component analysis. Application of organic fertilizers (T3 and T4) increased soil TOC levels. Chemical fertilizer treatment (T2) resulted in the highest shoot fresh weight, yield, and marketable root yield. Marketable stem diameter was positively influenced by T2 and T4. There were no significant treatment effects on plant height. Hierarchical clustering isolated organic fertilizers (T3 and T4) from other treatments. Principal component analysis revealed two principal components, which together explained 87.77% of the total variance. Organic fertilizer application provided the highest TOC accumulation during the experimental period, whereas NPK fertilization was the most effective in increasing cassava yield in the first year of cultivation.
Keywords: Cattle manure; Crop yield; Manihot esculenta; Organic fertilizer; Organic matter